T-cell receptor Vβ repertoire of CD8+ T-lymphocyte subpopulations in cutaneous leishmaniasis patients from the state of Rio de Janeiro, Brazil - Ferraz, Raquel (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Núcleo de Purificação Celular (Sorting). Plataforma de Citometria de Fluxo. Rio de Janeiro, RJ, Brasil.